GAYA STILISTIKA PUISI â€œPEREMPUAN SELALU INGATâ€ KARYA DIAN RENNUATI: KAJIAN KERELEVANSIAN DENGAN PEMBELAJARAN BAHASA INDONESIA DI SMA - Hidajati, Enny (Jurnal Ilmiah Bina Edukasi, 2020)
Dian Rennuati is a doctor and poet from Palembang. Dian is known to have a style of language (stylistic) which is very beautiful from the point of women. The poem under study entitled "Perempuan Selalu Ingat". The problem examined in this study is how the stylistic style of the poem "Perempuan Selalu Ingatâ€ and the relevancies of poem â€œPerempuan Selalu Ingatâ€ by Dian Rennuati as bahasa Indonesia teaching materials in high school. Therefore, this study aims to uncover the style of stylistics in the poem. This research is a type of library research using descriptive method. Based on research found five aspects of stylistics in poetry, namely diction, real words (concrete, denotative), images (images) majas (figuratively), rhythm and rhyme. Based on research that has been done, found the use of these five aspects. There is relevance poem as bahasa Indonesia learning materials in high school